Reflection loss minimization for a ZnO/CdS/CuInSe₂ photovoltaic cell - Abdelhakim Mahdjoub; Lazhar Hadjeris (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
A photovoltaic cell, based on copper and indium selenide (CuInSe₂) thin layers, with a good efficiency can be achieved by simple, easy to implement and low cost techniques. The high refractive index materials used as absorbers in photovoltaic cells cause high reflection losses (about 30%). Thin CdS and ZnO films that are, respectively, the buffer layer and the window of the cell have lower indices and are naturally suited to antireflective applications. Also, a suitable choice of the film thickness leads to minimization of reflection losses, resulting in a significant improvement of the photovoltaic efficiency. The aim of this work is to provide easy solutions that reduce reflection losses to less than 4% while respecting technological constraints.